Preparation and characterization of CuO-CoO-MnO/SiO2 nanocomposite aerogels as catalyst carriers - 赵越卿 赵海雷 梁英华 贾千一 张波波 (Transactions of Nonferrous Metals Society of China, 2010)
CuO-CoO-MnO/SiO2 nanocomposite aerogels were prepared by using tetraethyl orthosilicate （TEOS） as Si source, and aqueous solution of Cu, Co and Mn acetates as the precursors via sol-gel process and ethanol supercritical drying technique. The gelatination mechanism was investigated by nuclear magnetic resonance （NMR） and X-ray photoelectron spectroscopy （XPS）. The microstructure and composition of the CuO-CoO-MnO/SiO2 nanocomposite aerogels were characterized by field emission scanning electron microscopy （FE-SEM）, transmission electron microscopy （TEM）, electron dispersive spectroscopy （EDS） and XPS. The specific surface area, pore size and pore size distribution of the nanocomposite aerogels were determined by the Brunauer-Emmett-Teller （BET） method. The products were analyzed by gas chromatography （GC）. The results show that the CuO-CoO-MnO/SiO2 nanocomposite aerogels are porous, with a particle size distribution of 10-150nm, a pore size distribution of 2-16 nm, an average pore size of 7.68 nm, and a specific surface area of 664.4-695.8 m2/g. The molar fraction of transition metals in the nanocomposite aerogels is 0.71%-13.77%. This kind of structure is favorable not only to increase the loading of catalysts, but also to make full use of the effect of transition metal oxides as cocatalysts; CuO-CoO-MnO/SiO2 nanocomposite aerogels can be used as a novel catalyst carrier in the safer and environment-friendly synthesis of diphenyl carbonate and other fields of catalysis.